Evaluation of surface modified PLLA-collagen hollow fiber as vascular graft - Mayasari, Dita Ayu; Widiyanti, Prihartini; Rudyardjo, Djony Izak (Universitas Muhammadiyah Purwokerto, 2019)
Background: Cardiovascular disease as the first silent killer in the world is related to atherosclerosis plaque. Coronary artery bypass grafting as a gold standard for severe atherosclerosis needs alternative materials to replace the narrowed artery due to plaque. PLLA is one of the biodegradable polymers which is suitable for the vascular graft, but some of its weaknesses should be addressed.Objective: The aim of this research is to improve PLLA characteristics for a vascular graft candidate by using collagen and chitosan.Methods: This study was an experimental study that consisted of two steps, preparation of hollow fiber and evaluation of its characteristic. This research evaluated the effect of chitosan concentration against cytotoxicity and hemocompatibility using MTT assay and hemolytic test.Results: The result showed that chitosan could improve the biological characteristics of hollow fiber PLLA-collagen, non-toxic, and non-hemolytic.Conclusions: There is a good effect on the biological characteristics of PLLA-Collagen hollow fiber by adding chitosan on the surface of PLLA-Collagen hollow fiber.